Contributions to the knowledge of Ceratitis capitata Wied. (Diptera, Tephritidae) in Northern Italy II. Overwintering in Lombardy (Bollettino di zoologia agraria e bachicoltura, 2024)
During three winter seasons since the year 2000 until 2003, surveys have been held in order to study Ceratitis capitata overwintering potential in Lombardy (Northern Italy), an area classified outside the tephritid stable establishment limits. The surveys have been carried out on the field, over infested fruits and pupae, and in indoor environments, residential premises, with adults. The mortality rate was 100% for the larvae inside the fruits and for the pupae. The adults were able to overwinter in two winter seasons out of three. In 2000-01 about 45% of the specimens resulted to be still alive at the beginning of June, when the first ripe fruits appeared in the field. The last adults survived until the first half of August, after more than 260 days since the emergence. In 2002-03 survival rates at the beginning of June ranged from 0% to 85% and the last adults died in the first ten days of August, when they were more than 250 days old. The surviving females had laid fertile eggs from the beginning of June to August 1st in 2001 and to July 4th in 2003, from the 190th to the 250th day of life. These results together with some peculiar aspects of the Lombard fruit growing, showthat in indoor environments the adults could overwinter, giving birth to new populations the following spring.
Keywords: Medfly; Lombardy; Northern Italy; Overwintering; Adults; Indoor environment